Diseño arquitectónico de una sede municipal en la parroquia satelital La Aurora - Mariscal Caicedo, Juan Carlos (2023)
This is a way to recognize or identify problems that exist at the level of society such as the lack of a municipal headquarters in the satellite parish of La Aurora, referring to the level of municipal organizations. The main objective of this research is to carry out the study and design of an architectural proposal, which is aimed at the satellite parish of La Aurora for the development of a new municipal headquarters, since this public entity is responsible for managing, directing and inspecting municipal services and works, This is due to the fact that at present the municipal headquarters does not have the optimal conditions for the activities to be carried out in an adequate manner, in addition to the lack of work areas, the lack of spaces for the attention and waiting of its users, this has resulted in a lousy attention for its officials and for the users, who require more space and furniture according to the regulations. It is for this reason that through our architectural design we seek to improve the administrative services of the sector, and implement a building with a pioneering architecture benefiting the cultural and economic aspect of the sector.